Sodium battery positive electrode material and preparation method thereof
Patent Information
- Application Number
- CN202610827526.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-09
- Publication Date
- 2026-10-20
AI Technical Summary
[0025]高电压与高容量协同:通过分子级别的p型-双极性-n型单元集成,实现了>3.6 V放电平台与>186 mAh/g比容量的同时达成,能量密度高达478 Wh/kg,显著优于已有的COF钠电正极材料。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of sodium-ion battery technology, and more specifically, to a sodium-ion battery cathode material and its preparation method. Background Technology
[0002] Sodium-ion batteries are a next-generation rechargeable battery technology that uses sodium ions as charge carriers to store and release electrical energy. Compared to traditional lithium-ion batteries, sodium-ion batteries offer lower cost, wider availability of resources, and longer lifespan. This makes sodium-ion batteries important and widely used in energy storage, particularly in areas such as renewable energy integration, electric transportation, and energy storage systems.
[0003] Currently, sodium-ion battery cathode materials mainly include layered transition metal oxides, polyanionic compounds, Prussian blue analogs, and organic cathode materials. Among them, organic cathode materials have attracted widespread attention due to their structural diversity and resource sustainability. Covalent organic frameworks (COFs), as a novel class of crystalline porous polymers, form two-dimensional or three-dimensional structures through strong covalent bonds, which can effectively suppress the dissolution of active materials in electrolytes.
[0004] Among the reported COF cathode materials, n-type redox groups (such as C=O, C=N, imides, etc.) have high theoretical capacities, but their operating voltages are generally lower than 2.6 V (vs. Na). + The presence of / Na limits the energy density. P-type groups (such as triphenylamine and phenothiazine) can achieve voltage plateaus above 3.0 V, but their specific capacity is typically low. Bipolar groups (such as porphyrins and their metal complexes) possess both p-type and n-type characteristics, but existing porphyrin-based COF cathode materials have not yet achieved high-voltage discharge plateaus, and their energy density remains unsatisfactory.
[0005] In existing technologies, simply mixing p-type and n-type small molecules or using non-covalent composites is insufficient to address the problems of poor dissolution and cycling stability of active materials. Covalently integrating different electroactive units into the same COF framework and achieving synergistic effects among p-type, n-type, and bipolar units is a pressing technical challenge in this field. Summary of the Invention
[0006] The main objective of this invention is to improve the technical problem that existing sodium-ion cathode materials cannot synergistically achieve high voltage, high reversible specific capacity, high energy density, structural stability, and cycle performance. Based on this, a sodium-ion cathode material is provided.
[0007] Another object of the present invention is to provide a method for preparing the above-mentioned material.
[0008] To achieve the above objectives, the specific technical solution adopted by the present invention is as follows: This invention provides a sodium-ion battery cathode material that achieves a synergistic effect of a high voltage platform (>3.6 V) and high specific capacity (>180 mAh / g) by covalently integrating p-type triphenylamine units, bipolar metalloporphyrin units, and imine linking units into the same three-dimensional covalent organic framework. This also improves the structural stability and cycle life of the material and solves the problems of low energy density and poor cycle stability of existing COF cathode materials.
[0009] The sodium-ion cathode material is a three-dimensional covalent organic framework material, and its chemical structure includes the following three structural units: (1) p-type electroactive structural unit: Triphenylamine (TPA) unit or its derivatives, which adsorb / desorb PF6- anions in the electrolyte through a reversible one-electron redox reaction, providing a voltage higher than 3.6 V (vs. Na + The discharge platform of / Na); (2) Bipolar electroactive structural unit: metalloporphyrin unit, with the general formula M-Por, where M is selected from one or more of Cu, Co, Ni, Fe, Zn, and Mn, and Por is a porphyrin macrocycle; this unit can be oxidized to store PF6- in a 16π electronic state or reduced to store Na in a 20π electronic state. + Simultaneously, a reversible valence state change occurs at the metal center (e.g., Cu). 2+ / Cu + Contribute additional capacity; It should be noted that, according to the specific capacity formula C=26.8n / M, M=1015, the presence of divalent Cu can adsorb an additional 2 PF6-, so theoretically the additional capacity contribution is 52mAh / g.
[0010] (3) Connecting unit: imine bond (-C=N-) or borate ester, connecting the TPA unit and the metal porphyrin unit.
[0011] The molecular structure using borate esters as linking units is shown below:
[0012] The three-dimensional covalent organic framework has a non-intersecting truncated octahedral structure based on a (3,4)-connection topology model, with cell parameters of a = b = 62.5~63.5 Å, c = 43.0~44.0 Å, α = β = γ = 90°.
[0013] The specific surface area (BET) of the sodium-ion cathode material is 5~80 m² / g, preferably 10~40 m² / g; the tap density is 0.5~2.5 g / cm³.
[0014] When used as the positive electrode of a sodium-ion battery, it exhibits a discharge plateau higher than 3.6 V within a voltage window of 1.5 to 4.4 V; the reversible specific capacity at a current density of 50 mA / g is not less than 180 mAh / g, and the energy density is not less than 470 Wh / kg; after 2000 cycles at a current density of 0.5 A / g, the capacity retention rate is not less than 90%.
[0015] This invention also provides a method for preparing a sodium-ion cathode material, comprising the following steps: Step 1: Preparation of metalloporphyrin monomers (pre-metallization method) 5,10,15,20-tetra(4-aminophenyl)porphyrin (TAPP) and metal acetate (M(OAc)2, where M is selected from Cu, Co, Ni, Fe, Zn, Mn) were added to N,N-dimethylformamide (DMF) in a molar ratio of 1:2 to 1:5. The mixture was refluxed at 120-160°C for 8-24 hours under nitrogen protection. After cooling, the mixture was added to ice water to precipitate the metallized porphyrin monomer M-TAPP. The precipitate was then filtered, washed, and dried to obtain the metallized porphyrin monomer M-TAPP.
[0016] Step 2: Solvent-thermal synthesis of three-dimensional COF Weigh tris(4-formylphenyl)amine (TPA-3CHO) and M-TAPP obtained in step one, and add them to the reaction vessel at a molar ratio of (0.5~1.5):(0.5~1.5), preferably 1:1. Add an organic solvent and a catalyst. The organic solvent is selected from one or more mixed solvents selected from o-dichlorobenzene (o-DCB), n-butanol (n-BuOH), mesitylene, and 1,4-dioxane; the catalyst is a 3~12 M aqueous solution of acetic acid. After ultrasonically dispersing the mixture, perform a freeze-vacuum-thaw cycle for degassing (2~4 times), and seal the reaction vessel under vacuum.
[0017] Place the sealed container in an oven at 80~180℃ for 24~120 hours, preferably at 120℃ for 72 hours.
[0018] Step 3: Post-processing After the reaction was completed, the mixture was allowed to cool naturally to room temperature. The solid was collected by filtration and washed successively with tetrahydrofuran, acetone, and anhydrous ethanol. Then, it was subjected to Soxhlet extraction with acetone for 12–48 hours. The product was vacuum dried at 60–100 °C for 12–24 hours to obtain the sodium electrode material.
[0019] Optionally, the process also includes a step of combining with conductive carbon materials: mechanically mixing the above-mentioned COF material with conductive carbon black and carbon nanotubes (CNTs) at a mass ratio of (3~5):1, or adding CNTs in situ during the synthesis process (the amount added is 10~30% of the total precursor mass), so that COF grows in situ on the surface of CNTs.
[0020] In this invention, the triphenylamine unit has a strong electron-donating ability and is easily oxidized during charging to form a stable free radical cation (TPA). + • Meanwhile, the PF6- anions in the electrolyte are embedded in the framework to maintain electroneutrality. This p-type redox process occurs at a higher potential (>3.6 V), contributing a high voltage plateau.
[0021] Metalloporphyrin units possess a highly conjugated 18π-electron macrocyclic structure, enabling them to undergo both oxidation (losing electrons and storing PF6-) and reduction (gaining electrons and storing Na). + ), exhibiting bipolarity. Simultaneously, coordinating metal ions (such as Cu) 2+ It can be further reduced to Cu + It provides additional electron transfer.
[0022] The imine linker (-C=N-) is itself an n-type active site, which can be reversibly reduced at lower potentials and reacts with Na. + Combined, it contributes additional capacity.
[0023] The three active sites are covalently integrated into the same three-dimensional rigid framework, achieving a synergistic effect of "high-voltage p-type + high-capacity bipolar + additional n-type". The three-dimensional topological channels facilitate rapid ion diffusion, and the metal coordination enhances the structural stability of the framework, thereby achieving high energy density, excellent rate performance and ultra-long cycle life.
[0024] Compared with the prior art, the present invention has the following advantages:
[0025] High voltage and high capacity synergy: Through molecular-level p-type-bipolar-n-type unit integration, a discharge platform of >3.6 V and a specific capacity of >186 mAh / g are achieved simultaneously, with an energy density of up to 478 Wh / kg, which is significantly better than existing COF sodium cathode materials.
[0026] Ultra-long cycle stability: Metal ions (especially Cu) 2+ The coordination of the porphyrin ring with the COF enhances the rigidity and chemical stability of the COF framework. After 2000 cycles at a high current density of 0.5 A / g, the capacity retention rate reached 93.4%, and the crystallinity of the material remained intact after cycling, while the diffraction peaks of the comparative material almost disappeared.
[0027] Based on the above, the present invention also has the following features: Rapid dynamic characteristics: The three-dimensional open-pore structure endows the material with a high apparent sodium ion diffusion coefficient (8.91 × 10⁻⁶). -10 Up to 2.63×10 -13 cm 2 / s), charge storage is dominated by surface-controlled pseudocapacitive behavior (b value of about 0.95), thus exhibiting excellent rate performance (still maintaining 122 mAh / g at 2 A / g).
[0028] A clear mixed-ion storage mechanism: PF6- and Na+ were confirmed by in-situ FT-IR, ex-situ XPS, and DFT calculations. + The collaborative storage pathway provides theoretical guidance for the design of high-performance organic electrode materials.
[0029] Serialized tunability: By changing the metal type of the porphyrin center (Cu, Co, Ni, Fe, Zn, etc.), the discharge plateau, capacity, and cycle stability can be adjusted to meet different application requirements. Detailed Implementation
[0030] The present invention will be further explained and described below through specific embodiments. It should be understood that the purpose of the following embodiments is to make the technical solution of the present invention clearer and easier to understand, and does not limit the scope of protection of the claims.
[0031] The present invention will be further described below through specific embodiments.
[0032] Example 1: Preparation of copper porphyrin COF material (TPA-CuPor-COF) (pre-metallization route)
[0033] Step 1: Preparation of Cu-TAPP 5,10,15,20-tetrakis(4-aminophenyl)porphyrin (0.68 g, 1.0 mmol) and copper acetate (0.40 g, 2.0 mmol) were added to a three-necked flask containing 50 mL of dehydrated DMF, and refluxed at 140 °C for 12 hours under nitrogen protection. After cooling, the mixture was poured into 200 mL of ice water, filtered, washed with deionized water and methanol, and dried under vacuum at 60 °C for 12 hours to give a purplish-black solid in 92% yield.
[0034] Step 2: Synthesis of TPA-CuPor-COF Tris(4-formylphenyl)amine (42.9 mg, 0.1 mmol) and Cu-TAPP (71.3 mg, 0.1 mmol) were added to a Parker tube, followed by o-dichlorobenzene (0.8 mL), n-butanol (0.8 mL), and 6 M aqueous acetic acid solution (0.4 mL). The subsequent steps were the same as in Example 1. A dark brown solid was obtained in 78% yield with a BET surface area of 20.6 m² / g.
[0035] Example 2: Preparation of cobalt porphyrin COF material (TPA-CoPor-COF) Referring to Example 1, copper acetate was replaced with cobalt acetate (Co(OAc)₂·4H₂O, 0.50 g, 2.0 mmol), otherwise the same. Yield 76%, BET specific surface area 19.8 m². 2 / g.
[0036] Example 3: Preparation of nickel porphyrin COF material (TPA-NiPor-COF) Referring to Example 1, copper acetate was replaced with nickel acetate (Ni(OAc)₂·4H₂O, 0.50 g, 2.0 mmol), otherwise the same. Yield 77%, BET specific surface area 20.1 m². 2 / g.
[0037] Example 4: Preparation of zinc porphyrin COF material (TPA-ZnPor-COF) Referring to Example 1, copper acetate was replaced with zinc acetate (Zn(OAc)₂·2H₂O, 0.44 g, 2.0 mmol), otherwise the same. Yield 75%, BET specific surface area 19.5 m². 2 / g.
[0038] Example 5: Preparation of iron porphyrin COF material (TPA-FePor-COF) Referring to Example 1, copper acetate was replaced with ferrous acetate (Fe(OAc)₂, 0.35 g, 2.0 mmol), and the reaction was carried out in a strictly air-free environment. The yield was 73%, and the BET specific surface area was 18.9 m². 2 / g.
[0039] Example 6: Preparation of manganese porphyrin COF material (TPA-MnPor-COF) Referring to Example 1, copper acetate was replaced with manganese acetate (Mn(OAc)₂·4H₂O, 0.49 g, 2.0 mmol), otherwise the same. Yield 74%, BET specific surface area 19.2 m². 2 / g.
[0040] Example 7: Preparation of mixed metalloporphyrin COF (TPA-Cu / Co-Por-COF) Referring to Example 1, Cu-TAPP (0.05 mmol, 35.7 mg) and Co-TAPP (0.05 mmol, 35.7 mg) were mixed as a total amount of 0.1 mmol of porphyrin monomer, with the rest remaining the same. The yield was 76%, and the BET specific surface area was 19.6 m² / g.
[0041] Example 8: Preparation of CNT in-situ composite TPA-CuPor-COF Referring to Example 1, multi-walled carbon nanotubes (CNTs, 22.8 mg, 20% of the total precursor mass) were additionally added to the reaction mixture and ultrasonically dispersed until homogeneous. The rest were the same. The yield was approximately 80%, and the BET surface area was approximately 45 m² / g.
[0042] Example 9: TPA-CuPor-COF with different monomer molar ratios (TPA:Cu-TAPP=0.8:1) Referring to Example 1, the amount of tris(4-formylphenyl)amine was changed to 0.08 mmol (34.3 mg), while Cu-TAPP remained at 0.1 mmol (71.3 mg). The yield was 72%, and the BET specific surface area was approximately 22 m² / g.
[0043] Comparative Example 1: A physical mixture of triphenylamine small molecules and copper porphyrin small molecules Triphenylamine (25.0 mg), tris(4-formylphenyl)amine (42.9 mg), and Cu-TAPP (71.3 mg) were physically mixed using a planetary ball mill (300 rpm, 2 hours) without thermal polycondensation. The BET specific surface area was 2.5 m² / g.
[0044] Comparative Example 2: Preparation of Metal-Free Porphyrin COF Material (TPA-Por-COF) Tris(4-formylphenyl)amine (42.9 mg, 0.1 mmol) and 5,10,15,20-tetra(4-aminophenyl)porphyrin (67.3 mg, 0.1 mmol) were weighed and added to a 10 mL ampoule. o-Dichlorobenzene (0.8 mL), n-butanol (0.8 mL), and 6 M aqueous acetic acid solution (0.4 mL) were added. The mixture was ultrasonically dispersed for 10 minutes, and degassed three times using a freeze-vacuum-thaw cycle before being vacuum-sealed. The mixture was then placed in a 120 °C oven and reacted for 72 hours. After natural cooling, the mixture was filtered and washed successively with tetrahydrofuran, acetone, and anhydrous ethanol. The mixture was then Soxhlet extracted with acetone for 24 hours and dried under vacuum at 80 °C for 12 hours to obtain a brown powder, with a yield of 75%.
[0045] Comparative Example 3: Preparation of COF materials without p-type units Weigh 38.2 mg (0.1 mmol) of trimesin and 67.3 mg (0.1 mmol) of 5,10,15,20-tetra(4-aminophenyl)porphyrin into a 10 mL ampoule, add 0.8 mL of o-dichlorobenzene, 0.8 mL of n-butanol, and 0.4 mL of 6 M acetic acid aqueous solution. Disperse by sonication for 10 minutes, degass by freezing-vacuuming-thawing three times, and then seal under vacuum. Incubate at 120 °C for 72 hours. After natural cooling, filter, wash successively with tetrahydrofuran, acetone, and anhydrous ethanol, extract with acetone by Soxhlet extraction for 24 hours, and dry under vacuum at 80 °C for 12 hours to obtain a brown powder.
[0046] Comparative Example 4: Preparation of inert COF materials with no redox activity Weigh 38.2 mg (0.1 mmol) of trimesin and 34.3 mg (0.1 mmol) of 1,3,5-tris(4-aminophenyl) into a 10 mL ampoule, add 1 mL of o-dichlorobenzene, 1 mL of n-butanol, and 0.4 mL of 6 M acetic acid aqueous solution. Disperse by sonication for 10 minutes, degass by freezing-vacuuming-thawing three times, and then seal under vacuum. Incubate at 120 °C for 72 hours. After natural cooling, filter, wash successively with tetrahydrofuran, acetone, and anhydrous ethanol, extract with acetone by Soxhlet extraction for 24 hours, and dry under vacuum at 80 °C for 12 hours to obtain a reddish-brown powder.
[0047] Comparative Example 5: Shortening the reaction time yielded a sample with low crystallinity.
[0048] Specifically, as in Example 1, the reaction time was reduced to 12 hours.
[0049] Table 1: Performance of each item in the example
[0050] Table 2: Performance of Comparative Examples
[0051] By comparing the examples and comparative examples, it can be found that the overall performance of the examples, such as energy density, specific capacity, and cycle capacity retention, is superior to that of the comparative examples. Among them, Comparative Example 2, a COF material without metalloporphyrin, suffers from a low discharge voltage; Comparative Example 3, a COF material without p-type units, demonstrates the contribution of p-type triphenylamine units to the high voltage plateau; Comparative Example 4, an inert COF material without redox activity, indicates that the electrochemical activity originates from p-type / bipolar / n-type units rather than the framework itself; Comparative Example 5, with its shortened reaction time, illustrates the importance of high crystallinity for electrochemical performance under the combined influence of preparation method and molecular structure.
[0052] This invention has been described by way of embodiments, but does not constitute a limitation thereof. Other variations of the disclosed embodiments, which are readily apparent to those skilled in the art, should fall within the scope of the claims of this invention, with reference to the description of this invention.
Claims
1. A sodium-ion battery cathode material, characterized in that: Including three-dimensional covalent organic frameworks, The three-dimensional covalent organic framework is mainly composed of p-type electroactive structural units, bipolar electroactive structural units, and connecting units; The p-type electroactive structural unit is used to provide a discharge platform with a discharge voltage higher than 3.6V, and includes molecules containing triphenylamine functional groups and aldehyde groups; The bipolar electroactive structural unit includes PF6, which can be oxidized to a 16π electron state for storage. - It can also be reduced to the 20π electronic state to store Na. + Meanwhile, the metal center undergoes a reversible valence state change, contributing additional capacity to the metal porphyrin unit.
2. The sodium-ion cathode material according to claim 1, characterized in that: The general formula of the metalloporphyrin unit is M-Por, where M is selected from one or more of Cu, Co, Ni, Fe, Zn or Mn, and Por is a porphyrin macrocycle.
3. The sodium-ion cathode material according to claim 1, characterized in that: The connecting unit is an imine bond or a borate ester.
4. The sodium-ion cathode material according to claim 1, characterized in that: The three-dimensional covalent organic framework has a non-intersecting truncated octahedral structure based on a (3,4)-connection topology model, with cell parameters of a = b = 62.5~63.5 Å, c = 43.0~44.0 Å, α = β = γ = 90°.
5. The sodium-ion cathode material according to claim 1, characterized in that: The specific surface area of the sodium-ion cathode material is 5~80 m² / g.
6. The sodium-ion cathode material according to claim 1, characterized in that: The specific surface area of the sodium-ion cathode material is 10~40 m² / g.
7. The sodium-ion cathode material according to claim 1, characterized in that: The tap density of the sodium-ion cathode material is 0.5~2.5 g / cm³.
8. A preparation method according to any one of claims 1-7, characterized in that: Includes the following steps: Step 1: Preparation of metalloporphyrin monomers 5,10,15,20-tetra(4-aminophenyl)porphyrin and metal acetate were added to N,N-dimethylformamide in a molar ratio of 1:2 to 1:
5. The mixture was refluxed at 120 to 160 °C for 8 to 24 hours under nitrogen protection. After cooling, the mixture was added to ice water to precipitate the metallized porphyrin monomer M-TAPP. Step 2: Solvent-thermal synthesis of three-dimensional COF Weigh tris(4-formylphenyl)amine (TPA-3CHO) and M-TAPP obtained in step one, and add them to the reaction vessel at a molar ratio of (0.5~1.5):(0.5~1.5); Add organic solvents and catalysts; After ultrasonic dispersion of the mixture, it is subjected to a freezing-vacuuming-thawing cycle for degassing (2-4 times), and the reaction vessel is sealed under vacuum. Place the sealed container in an oven at 80~180℃ and react for 24~120 hours; Step 3: Post-processing After the reaction was completed, the mixture was allowed to cool to room temperature naturally. The solid was collected by filtration and washed successively with tetrahydrofuran, acetone and anhydrous ethanol. Then, it was extracted with acetone by Soxhlet extraction for 12-48 hours. The product was vacuum dried at 60~100℃ for 12~24 hours to obtain the sodium-ion cathode material.
9. The preparation method according to claim 8, characterized in that: It also includes the step of combining with conductive carbon materials: The above-mentioned COF material is mechanically mixed with conductive carbon black and carbon nanotubes (CNTs) at a mass ratio of (3~5):1, or CNTs are added in situ during the synthesis process (the amount added is 10~30% of the total precursor mass) so that COF grows in situ on the CNT surface.
10. The preparation method according to claim 8, characterized in that: In step two, tris(4-formylphenyl)amine (TPA-3CHO) and M-TAPP obtained in step one are weighed and added to the reaction vessel at a molar ratio of 1:
1. The organic solvent is selected from one or more mixed solvents selected from o-dichlorobenzene (o-DCB), n-butanol (n-BuOH), mesitylene, or 1,4-dioxane; The catalyst is a 3-12 M aqueous solution of acetic acid; Place the sealed container in a 120°C oven for 72 hours to react.